Export Management Approach for Nepal - Regmi, Suman Kumar (Administration and Management Review, 2012)
The objective of this paper is to show the export management approach for Nepal as envisaged in the development plans, policies, and programs. Some useful lessons of Asian experiences on economic development are also pointed out in the context of Nepal's endeavors towards economic development. Export growth model sketch has been used to show export trade scenario. It also highlights major issues of export management in Nepal drawing the conclusion from the periodic plans, trade policy and Nepal Trade Integration Strategy (NTIS). Administrative and Management Review Vol. 24, No. 2, August 2012, Page 65-76